2007
DOI: 10.1111/j.1468-0122.2007.00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing Capacity for Social and Emotional Growth: An Action Research Project

Abstract: This article reports an action research project in which children, their teacher and the author, and an advisory teacher from a Local Authority collaborated as co-researchers in a project to improve working relationships in the classroom. Both appreciative enquiry and emancipatory research informed the project. This article focuses on one aspect of the project: the development of active listening skills. In an initial consultation, the teacher described her difficulty in teaching a mixedyear class of 7-9-year-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Untrained teachers may engage in practices which go against the humanistic principles underlying CT, such as pupil empowerment, democracy, equity and unconditional positive regard (Doveston, 2007;Taylor, 2003). Staff will need to be convinced, for instance, of student empowerment, if they are to engage in good practice with student-directed learning (Cefai & Cooper, 2010;Cremin, 2002;Leach & Lewis, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Untrained teachers may engage in practices which go against the humanistic principles underlying CT, such as pupil empowerment, democracy, equity and unconditional positive regard (Doveston, 2007;Taylor, 2003). Staff will need to be convinced, for instance, of student empowerment, if they are to engage in good practice with student-directed learning (Cefai & Cooper, 2010;Cremin, 2002;Leach & Lewis, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Aguis, 2011;Hennessey, 2007;Kulchy, 2009;Tew, 1998). Other studies which made use of a multi-strategy approach, including CT, similarly reported improvements in emotional literacy and social skills such as listening and speaking (Coppock, 2007;Doveston, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…In the school setting there have been studies which have focused on improving children's listening and social skills [35][36][37][38], since educators have been complaining about their students' inability to listen carefully and pay attention. However, adults' listening skills are often also insufficient and teachers may have higher expectations from children than they do from themselves.…”
Section: Teachers' Listening and Active Listening Skillsmentioning
confidence: 99%
“…Childconferencing is a type of informal structured interview, commonly referred to as a focus group (Dupree, Bertram, andPascal 2001 as cited in Clark 2005;Norton 2006;Smith, Duncan, and Marshall 2005). Group interviews are more informal than childconferencing; they are discussions with children about specific topics (Doveston 2007;Huber and Clandinin 2002;Messiou 2006aMessiou , 2006bParkes 2008;Rogers and Evans 2007;Smith, Duncan, and Marshall 2005;Thomson, Hall, and Russell 2007). For some children it is less intimidating to be interviewed in a group instead of oneon-one (Clark 2005).…”
Section: Focus Groups and Group Interviewsmentioning
confidence: 97%
“…Listening to and interacting with children can provide new insights including influencing educational and social policy and practice (Clark 2005;Parkes 2008). Including children in school-based research may lead to changes in intervention strategies, the curriculum and classroom rules (Daigle, Hebert, and Humphries 2007;Doveston 2007;Messiou 2006b;Rogers and Evans 2007).…”
Section: Emerging Thinking About Children and Researchmentioning
confidence: 98%